THE EFFECT OF MINERAL WATER AND RUNNING 400 METERS 3×3 ON PULSE RATE - Septiansyah, Horga Praja; Gandasari, Maharani Fatima (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This study aims to investigate the effect of mineral water consumption and physical activity in the form of running 400 meters (3 rounds 3 times) on a person's pulse rate and the difference in pulse rate for each set. The implementation of the test was carried out in the running track of the SSA pontianak stadium, this study checked the pulse before carrying out the test for 10 seconds, after which a light jogging warm-up for 10 minutes and continued by doing the test that had been determined. The research was conducted by measuring the subject's pulse before and after consuming mineral water, as well as before and after undergoing physical activity in the form of running 400 meters for 3 rounds 3 times. With a data collection method of one shot case study, the sample taken was 10 people, 6 men and 4 women from students of Sports Coaching Education (PKO) Tanjungpura University Pontianak. The data obtained was analyzed using the ANOVA test using the SPSS application. The results analyzed by the ANOVA test showed that there was no significant difference, the results showed a significance value of 0.357> 0.05, therefore it can be concluded that 240ml mineral water does not have a significant effect on pulse performance when doing more effort than usual. This study provides insight into how mineral water consumption and physical activity can affect a person's pulse rate, which is important for further understanding of cardiovascular health